Preoperative embolization of the splenic artery in patients that underwent splenectomy for immune thrombocytopenic purpura - Baú,PlínioCarlos (2007)
Transfusion of platelets, red blood cells, or both is usually necessary immediately after splenic artery ligature in patients with immune thrombocytopenic purpura who undergo splenectomy. PURPOSE: To investigate whether preoperative embolization of the splenic artery reduced the need for transfusion of platelets, red blood cells, or both. METHODS: Twenty- seven consecutive patients that underwent splenectomy for purpura between October 1999 and March 2006 performed by the same surgical team were enrolled. The first 17 patients did not undergo embolization and were compared with the next 10 patients, who composed the embolization group. RESULTS: The platelet count in the embolization group rose from a mean 7000 u/µl before to 75000 u/µl after the procedure. There was no need for platelet or red blood cell transfusion in the embolization group; in the group without preoperative embolization, 11 patients (p=0.001) required platelet transfusion and 8 (p=0.01), red blood cell transfusion. CONCLUSION: Embolization of the splenic artery before splenectomy is a safe method to avoid blood transfusions in patients with ITP.